2001
DOI: 10.1523/jneurosci.21-16-06338.2001
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Increases in Nucleus Accumbens Dopamine after Systemic Cocaine Administration Are Caused by Unique Characteristics of Dopamine Neurotransmission

Abstract: In vivo voltammetry was used to investigate the preferential increase of extracellular dopamine in the nucleus accumbens relative to the caudate-putamen after systemic cocaine administration. In the first part of this study, cocaine (40 mg/kg, i.p.) was compared with two other blockers of dopamine uptake, nomifensine (10 mg/kg, i.p.) and 3␤-( p-chlorophenyl)tropan-2␤-carboxylic acid p-isothiocyanatophenylmethyl ester hydrochloride (RTI-76; 100 nmol, i.c.v.), to assess whether the inhibitory mechanism of cocain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
134
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(161 citation statements)
references
References 47 publications
(60 reference statements)
25
134
2
Order By: Relevance
“…The greater increase in dopamine after cocaine in females is consistent with the theoretical simulations of Wu et al (2001a) which show that cocaine should induce greatest percent increases in dopamine efflux in regions where release rates are lower and uptake rates are higher. Analysis of present baseline data from the cocaine-treated rats indicated that V max was 93% higher in females than in males, and [DA] p was 65% higher in females.…”
Section: Discussionsupporting
confidence: 85%
“…The greater increase in dopamine after cocaine in females is consistent with the theoretical simulations of Wu et al (2001a) which show that cocaine should induce greatest percent increases in dopamine efflux in regions where release rates are lower and uptake rates are higher. Analysis of present baseline data from the cocaine-treated rats indicated that V max was 93% higher in females than in males, and [DA] p was 65% higher in females.…”
Section: Discussionsupporting
confidence: 85%
“…Animal studies suggest that this reflects regional differences in drug-induced increases in synaptic DA levels (Di Chiara and Imperato, 1988) rather than an artifact of the PET method. Mechanisms proposed to mediate this preferential effect include regional variability in DA release, and in the density and activity of DA transporters and DA cell innervation (Haber and McFarland, 1999;Wu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript which are associated with its rewarding and stimulating properties [10,18,29,30]. Using FSCV coupled with kinetic analysis, cocaine has been found to act as a competitive inhibitor of DA uptake by altering K m [10,11,[18][19][20]29,30].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%